Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1530/joe-16-0367
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical leanness in the imprinting-centre deletion mouse model for Prader–Willi syndrome

Abstract: Prader–Willi syndrome (PWS), a neurodevelopmental disorder caused by loss of paternal gene expression from 15q11–q13, is characterised by growth retardation, hyperphagia and obesity. However, as single gene mutation mouse models for this condition display an incomplete spectrum of the PWS phenotype, we have characterised the metabolic impairment in a mouse model for ‘full’ PWS, in which deletion of the imprinting centre (IC) abolishes paternal gene expression from the entire PWS cluster. We show that PWS-ICdel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…Mir-92a-3p, which is reported to be inversely correlated with the human brown adipose tissue (BAT) activity [27], has been suggested as a potential serum biomarker for BAT in mice and humans. A mouse model with a deletion of the imprinting center (PWS-IC del mouse), shows an increased lipid utilization in BAT [28], however this experimental model is characterized by an incomplete phenotype of the syndrome, with reduced body weight. On the other hand, no data about BAT are currently available in patients with PWS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mir-92a-3p, which is reported to be inversely correlated with the human brown adipose tissue (BAT) activity [27], has been suggested as a potential serum biomarker for BAT in mice and humans. A mouse model with a deletion of the imprinting center (PWS-IC del mouse), shows an increased lipid utilization in BAT [28], however this experimental model is characterized by an incomplete phenotype of the syndrome, with reduced body weight. On the other hand, no data about BAT are currently available in patients with PWS.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could involve not only lipid profiles but also lipid accumulation in the liver. Indeed, Golding et al [28] showed that the hepatic lipid storage in a PWS-IC del mice was disrupted with a fewer but larger lipid droplets compared to the wild type. It is worth noting the finding of major differences in PWS compared to OB when considering the presence of steatosis grade 1.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic deletion in the mouse’ chromosome 7C creates a hyperphagic phenotype (Duker et al, ; Kantor, Shemer, & Razin, ) which is relatively homologous with the human PWS paternally deleted chromosome 15. However, the animal does not become obese as is the case with all mouse models replicating genetic deletions from the PWS critical region (Bervini & Herzog, ; Golding, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that hyperphagic feeding in the Snord116del mice is due to enhanced NPY activity (Bervini & Herzog, 2013;Zhang, Bouma, McClellan, & Tobet, 2012); we therefore targeted the melanocortin appetite pathway (Komarnytsky et al, 2013) via the 5-HT2c receptor to firstly determine homeostatic balance with NPY (Heisler et al, 2006;Zhou et al, 2005) and to discover whether CFE signaling involved this receptor. As this receptor has been reported to be disrupted in humans with PWS (Angulo, Butler, & Cataletto, 2015;Isles, 2017;Kishore & Stamm, 2006;Stamm, Gruber, Rabchevsky, & Emeson, 2017), it is important to understand whether CFE's action involves this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have revealed features of PWS not commonly reported in humans. For example, our study of metabolic homeostasis in the PWS-IC del mouse, in which paternal inheritance of an imprinting centre (IC) deletion results in a complete lack of gene expression from the entire PWS interval (Chamberlain et al, 2004), revealed overactive brown fat and excess heat production (Golding et al, 2017). Unlike humans with PWS (Kahn et al, 2018), PWS-IC del mice display profound abdominal leanness, probably resulting from a compromised capacity of PWS adipocytes to import lipid (Golding et al, 2017), a phenomenon reported in isolated human PWS adipocytes (Cadoudal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%